Secured Forensics Reporting Web Based on Two Factor Authentication - Sivakumaran, Sanishaa Nair; Abdullah, Zubaile (Applied Information Technology And Computer Science, 2022)
Computer forensics emerges in response to the escalation of computer and Internet crimes. The main focus in this project is on the final step of computer forensics which is the reporting stage. At the moment forensics analysts at Chiteeram Solution tend to use manual methods and third party tools which are single authenticated to perform computer forensics investigation. Hence, the security of web reporting is less secure. This project is proposed to tighten the web reporting document based on two factor authentication which is One Time Password (OTP)  via email and recaptcha at user login. These provided  an extra security layer  to secure user accounts. The methodolody of this project is using Waterfall Model and using PHP Codeigniter Framework. In order to test the security performance of this project, SQL injection syntax is performed to see the security strength of password  whereas md5hashing.net is used to test the strength of pdf password. . The application allows users to encrypt or decrypt the generated forensics report. There is also strong password management to ensure the confidentiality of the system.